2019
DOI: 10.1002/ird.2321
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Water Use, Energy Use And Carbon Emissions In Lift‐ Irrigated Areas: A Case Study From Karshi Steppe In Uzbekistan

Abstract: The advantages of a nexus approach in addressing complex environmental challenges are becoming increasingly clear. In Central Asia, however, the nexus between water–food–energy has not received adequate attention, as the very few studies that have been conducted fell short of quantifying nexus trade‐offs and benefits at a practical, small scale. This paper applies a quantitative accounting method to assess water and energy use intensity in irrigated areas of the Karshi Steppe of Central Asia that are supplied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Obviously, our research area is a typical counterexample. Since almost all of the regional irrigation water comes from the Amudarya River, the exploitation of groundwater is rare, and backwards water resource management methods (Djumaboev et al, 2019;Karthe et al, 2015) have caused it to be different from the global trend. This provides a good example that tells us that although the exploitation of groundwater has caused many irrigation areas to face many ecological problems, groundwater should be exploited appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, our research area is a typical counterexample. Since almost all of the regional irrigation water comes from the Amudarya River, the exploitation of groundwater is rare, and backwards water resource management methods (Djumaboev et al, 2019;Karthe et al, 2015) have caused it to be different from the global trend. This provides a good example that tells us that although the exploitation of groundwater has caused many irrigation areas to face many ecological problems, groundwater should be exploited appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…The Central Asian experts brought expertise on the WEF challenges and possible future development pathways but mostly lacked systems research experience on how to conceptualize the WEF nexus challenge for an SIA. Irrigated agriculture was selected as an overarching topic given it is an illustrative, cross-scale example of WEF nexus problems (Djumaboev et al 2019) and its central relevance for food production and economic well-being in Central Asia (Hamidov et al 2016). The geographic extent of the case studies ranged from international transboundary watersheds to very local scales, with a diversity of actors and sectorial focal issues.…”
Section: Methodsmentioning
confidence: 99%
“…Central Asia also has high energy use for irrigation due to pumping of water to a considerable height. Significant improvements are shown to be possible by Djumaboev et al (2019) who found that by better irrigation scheduling alone, more than 575 MCM (million cubic metres) and 259 GWh can be saved.…”
Section: Energy For Food and Watermentioning
confidence: 99%